A GOOD ADVISOR. (5th December 2018) - Berg, Nathan; Kim, Jeong‐Yoo
ABSTRACT: Effective education requires strategic consideration. If students doubt the motives of teachers and advisors, then students rationally ignore the advice they receive. Valuable information is lost in such bad communication outcomes and, consequently, the quality of education suffers. In this paper, we argue that an advisor's sacrifice is an essential virtue of a good advisor for efficient communication between an advisor and a student. We model the relation between them as a signaling game. We find a separating equilibrium in which a good advisor (whose objective function truly coincides with the student's own objective function) makes a costly sacrifice that causes the student to believe what the advisor says, while a non‐good advisor (whose objective does not coincide with the student's) chooses not to make the costly sacrifice and, consequently, the student completely ignores the advisor. In fact, it turns out to be the unique equilibrium that survives the Intuitive Criterion. The model demonstrates the importance of making students aware of those aspects of the advisor's objectives that students may not realize are closely aligned with their own (e.g., the extent to which an advisor cares about students' academic and professional trajectories as evaluated by students themselves).